DETERMINAN AKUNTABILITAS LAPORAN KEUANGAN YAYASAN PONDOK PESANTREN - Amnaniwati; Siti Aisyah Hidayati; Ahmad Rifai (Universitas Mataram, 2022)
The research was conducted to analyze the effect of trust, transformational leadership, human resource competency and internal control systems on financial reporting accountability. The population and research sample are members who are members of the working group of the Madrasah aliyah Nahdlatul Wathan Central Lombok. This research is a quantitative research with data processing methods using IBM SPSS Statistics25. The results of the study show that trust, transformational leadership and human resource competence do not affect the accountability of Islamic boarding schools' financial reports. In contrast to the internal control system which affects the accountability of financial reports.